Preparation method and application of 3D printing functional protein nano composite material

The preparation of functional protein-loaded iron oxide nanocomposites through 3D printing technology has solved the shortcomings in the existing technology in particle size control, dispersion stability and structure customization when treating phosphorus-containing wastewater, and achieved the effect of efficiently removing low-concentration phosphorus.

CN119771359AInactive Publication Date: 2025-04-08NANJING SHANGSHAN ENVIRONMENTAL ENG TECH CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411961446.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When treating phosphorus-containing wastewater, the prior art has shortcomings in particle size control, dispersion stability and structure customization, making it difficult to efficiently remove low-concentration phosphorus.

Method used

Functional protein-loaded iron oxide nanocomposites were prepared by 3D printing technology, sub-10 nm iron oxide-functional protein composite particles were generated in situ by solvothermal method, and composite materials with controllable pore structures were constructed through 3D printing.

Benefits of technology

It realizes efficient removal of low-concentration phosphorus in phosphorus-containing wastewater, and the material still maintains an efficient removal rate after multiple uses, reducing the replacement frequency and cost during water treatment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a 3D printing functional protein nano composite material, and the preparation method comprises the following steps: (1) in-situ generation of iron oxide-functional protein composite particles: selecting functional protein, and carrying out self-assembly to form a fibrous structure; the method comprises the following steps: mixing functional protein with an iron salt solution, performing in-situ synthesis through a chemical reaction to obtain iron oxide nanoparticles with the particle size of less than 10nm, and uniformly distributing the iron oxide nanoparticles on the surface of the functional protein; (2) 3D printing forming and heat treatment: dispersing the functional protein loaded iron oxide nanoparticles in the stable dispersion liquid, and forming a composite material with a controllable pore structure through 3D printing equipment; and carrying out vacuum drying and heat treatment on the printed composite material. The adsorption performance and regeneration capacity of the composite material are improved, the wastewater treatment efficiency can be effectively improved, and the composite material has high economical efficiency and environment friendliness, is suitable for deep phosphorus removal in a complex water body environment and can be widely applied to the fields of environment catalysis and resource recovery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmentally friendly water treatment and 3D printing, and in particular to a preparation method and application of a 3D printing functional protein nanocomposite material. Background Art

[0002] Water pollution, especially pollution caused by phosphorus, has become an important environmental issue closely related to human health and ecological environment. The irrational use of phosphorus-containing pesticides in agricultural production and the large-scale use of phosphorus-containing detergents in daily life are important sources of phosphorus-containing wastewater. This type of pollution not only promotes eutrophication of water bodies and seriously affects the development of fisheries, but may also destroy the ecological balance, lead to imbalance in the food chain, and ultimately threaten the human living environment. Therefore, the development of effective deep purification technology for phosphorus in water is of great significance for maintaining ecological security and human health.

[0003] At present, the treatment methods for phosphorus-containing wastewater mainly include chemical precipitation, biological method and adsorption method. The chemical precipitation method is simple to operate and has high treatment efficiency, but it is expensive and prone to secondary pollution. The biological method has strict requirements on reaction conditions and is more suitable for treating medium and low concentration phosphorus-containing wastewater, and its reaction rate is slow. In contrast, the adsorption method uses porous adsorbents with a large specific surface area to remove phosphorus from wastewater, which has the advantages of stable treatment effect, simple process and convenient operation. Therefore, the development of ideal adsorbents has become a key research content in the current treatment of phosphorus-containing wastewater. Recent studies have shown that nano-iron oxide (Fe2O3) has a strong effect on inorganic phosphorus, a fast adsorption rate, and the advantage of efficient phosphorus removal, making it a very promising material in the adsorption method.

[0004] In recent years, functional protein materials have been widely developed and applied in the field of environmental protection, especially bovine serum albumin and lysozyme protein. These proteins can form ultra-long flexible fibrous structures through simple heat treatment, called amyloid fiber structures. The surface of this structure is rich in polyamino components, which enables it to form strong interactions with a variety of ions, thus showing excellent performance in the field of water treatment.

[0005] Studies have shown that these functional protein materials have good coordination ability with iron, especially their disulfide structure enables the material to form a charged interface. This feature promotes the generation of sub-10 nm active iron oxide, significantly improving the material's ability to purify and remove phosphorus ions in water. The composite material formed by combining functional proteins with iron not only improves the removal efficiency of phosphorus in water, but also has good regeneration ability, and can maintain a high treatment performance after multiple uses.

[0006] With the development of materials science, 3D printing technology has gradually been applied to the field of environmental governance, especially in the design and preparation of new materials, showing great potential. 3D printing can accurately design the pore structure and specific surface area of ​​materials according to specific needs, significantly improve the physical and chemical properties of materials, and thus enhance their ability to remove specific pollutants.

[0007] Therefore, the development of a 3D printed functional protein nanocomposite material to deeply remove phosphorus from water has important theoretical significance and application value, and will provide a new solution for water treatment. Summary of the invention

[0008] The present invention proposes a preparation method and application of a 3D printed functional protein nanocomposite material, aiming to overcome the shortcomings of traditional phosphorus removal materials in terms of particle size control, dispersion stability and structural customization. The method can prepare a functional protein-loaded iron oxide composite material with high specific surface area, fine pore structure and good dispersibility, thereby showing excellent performance in applications such as deep phosphorus removal, environmental catalysis and magnetic separation, and is particularly suitable for efficient removal of low-concentration phosphorus in phosphorus-containing wastewater.

[0009] A method for preparing a 3D printed functional protein nanocomposite material, comprising the following steps: Step (1) in situ generation of iron oxide-functional protein composite particles: pre-treating the functional protein into a fibrous amyloid structure; mixing an iron salt solution with the material after the functional protein pre-treatment, and reacting them under a high temperature and high pressure environment of 105° C. to 115° C. for 3 to 5 hours, so that iron oxide nanoparticles with a particle size of less than 10 nanometers are evenly distributed on the surface of the functional protein fiber matrix, thereby obtaining functional protein-loaded iron oxide nanoparticles; Step (2) 3D printing and heat treatment: dispersing the functional protein-loaded iron oxide nanoparticles in a stable dispersion, and forming a composite material with a controllable pore structure through a 3D printing device; vacuum drying and heat treating the printed composite material to enhance the mechanical properties and chemical stability of the composite material.

[0010] An application of the 3D printed functional protein nanocomposite material of the present invention is used to treat phosphorus-containing wastewater.

[0011] The present invention provides a preparation method and application of a 3D printed functional protein nanocomposite material, which has the following obvious advantages over the existing process: Precise control of nanostructure and macroscopic morphology: The present invention generates sub-10 nm iron oxide-functional protein composite particles in situ through a solvothermal method, and combines 3D printing technology to accurately construct the macroscopic morphology of the material, which not only achieves uniform distribution and size control of iron oxide particles, but also can construct porous and complex 3D structures according to actual needs, which is beneficial to improving adsorption and catalytic performance.

[0012] Superior phosphorus adsorption performance: The composite material has strong adsorption and removal efficiency for phosphorus ions with the support of high specific surface area through the multi-amino sites of functional proteins and the high reactivity of iron oxide, and is suitable for deep phosphorus removal from wastewater. Compared with traditional adsorbents, the material can still maintain a high removal rate after multiple uses, greatly reducing the replacement frequency and cost in the water treatment process.

[0013] Green, environmentally friendly and low-cost: The present invention uses non-toxic, environmentally friendly functional proteins and iron salt raw materials, and the preparation process avoids the use of high temperature and highly toxic chemicals, which meets the green manufacturing standards. 3D printing technology makes the material preparation process simple and efficient, with low energy consumption and obvious cost advantages, suitable for industrial-scale production, and meets the needs of environmental protection applications.

[0014] Wide application potential in environmental governance: The iron oxide-functional protein composite material of the present invention not only performs well in wastewater phosphorus removal, but also has application potential in magnetic separation, pollutant degradation and energy materials (such as batteries and supercapacitors), providing a feasible green solution for wastewater treatment, soil remediation, clean energy, etc.

[0015] Excellent regeneration and reuse performance: The material maintains more than 90% adsorption efficiency and structural integrity after multiple cycles of regeneration, has high stability and anti-loss properties, and effectively reduces the long-term use cost of wastewater treatment. The good dispersibility of iron oxide particles and the stability of functional proteins give the material continuous high-efficiency performance in repeated use, which is particularly suitable for long-term environmental purification needs. DETAILED DESCRIPTION

[0016] The present invention is described in detail below in conjunction with specific implementation modes.

[0017] A method for preparing a 3D printed functional protein nanocomposite material comprises the following steps: Step (1) in situ generation of iron oxide-functional protein composite particles: pre-treating the functional protein into a fibrous amyloid structure; pre-treating the functional protein (such as bovine serum albumin or lysozyme) into a fibrous amyloid structure to increase the specific surface area and the exposure rate of the amino group, thereby enhancing the loading capacity of the iron oxide nanoparticles; The iron salt solution is mixed with the material pretreated with the functional protein, and reacted under a high temperature and high pressure environment of 105°C to 115°C for 3 to 5 hours, so that iron oxide nanoparticles with a particle size of less than 10 nanometers are evenly distributed on the surface of the functional protein fiber matrix, thereby obtaining functional protein-loaded iron oxide nanoparticles.

[0018] The iron salt used in step (1) is Fe(NO3)3·9H2O, which is dissolved in ethylene glycol or deionized water, and the solution concentration is 0.5 to 1.25 M, preferably in the range of 0.75 to 1.0 M.

[0019] Step (2) 3D printing and heat treatment: dispersing the functional protein-loaded iron oxide nanoparticles in a stable dispersion, and forming a composite material with a controllable pore structure through a 3D printing device; vacuum drying and heat treating the printed composite material to enhance the mechanical properties and chemical stability of the composite material.

[0020] The concentration of the dispersion in step (2) is 5% to 15%, and a dispersing aid accounting for 1% to 10% of the mass of the iron oxide is added to enhance the uniform distribution of the particles. The dispersing aid is polyethylene glycol or polyvinyl pyrrolidone, and the dispersing aid accounts for 3% to 5% of the mass of the iron oxide.

[0021] The 3D printing parameters in step (2) include an exposure time of 1 to 10 seconds and a layer thickness of 0.01 to 0.1 mm to achieve precise control of the material structure.

[0022] The heat treatment temperature in step (2) is 100° C. to 130° C., preferably 110° C. to 120° C., and the treatment time is less than 2 hours.

[0023] An application of the 3D printed functional protein nanocomposite material of the present invention is to treat phosphorus-containing wastewater.

[0024] The 3D printed functional protein nanocomposite material of the present invention can show a phosphorus removal rate higher than 85% in the treatment process of phosphorus-containing wastewater, and has good regeneration ability, and can be recycled multiple times after simple cleaning or low-temperature treatment.

[0025] The technical solution adopted by the present invention to achieve the above-mentioned purpose is as follows: A method for preparing a 3D printed functional protein nanocomposite material comprises the following steps: Step (1) In situ generation of iron oxide-functional protein composite particles: First, the functional protein material (such as bovine serum albumin or lysozyme protein) is pretreated under appropriate conditions to form a fibrous amyloid structure, increase the specific surface area and the exposure of multiple amino groups, so as to improve the loading capacity of iron oxide nanoparticles. Subsequently, an iron salt (such as Fe(NO3)3·9H2O) is dissolved in ethylene glycol or deionized water to prepare a solution with a concentration of 0.5 to 1.25 M (preferably 0.75 to 1.0 M), mixed with the functional protein material and transferred to an autoclave. The reaction is heated at 105°C to 115°C for 3 to 5 hours to in situ generate sub-10 nm iron oxide nanoparticles and evenly distribute them on the surface of the functional protein matrix. After the reaction is completed, the product is cooled to room temperature, repeatedly washed with deionized water and ethanol to remove impurities, and then centrifuged (8000 to 12000 rpm, preferably 10000 rpm) to obtain high-purity iron oxide-functional protein composite particles. Finally, the separated particles are dried under vacuum conditions at 50° C. to 80° C. to obtain composite nanoparticles with stable structure and uniform particle size.

[0026] Step (2) 3D printing and heat treatment: The prepared iron oxide-functional protein composite nanoparticles are dispersed in a solution to prepare a stable dispersion with a concentration of 5% to 15%. A dispersion aid (such as polyethylene glycol (PEG) or polyvinyl pyrrolidone (PVP)) accounting for 1% to 10% (preferably 3% to 5%) of the iron oxide mass can be added as needed, and ultrasonic dispersion and stirring are performed for 30 to 60 minutes to ensure uniform distribution of the particles. The dispersion is loaded into a photocurable 3D printing device, and the structure is precisely determined by controlling the printing parameters (including exposure time of 1 to 10 seconds, layer thickness of 0.01 to 0.1 mm and scanning speed). After printing, the composite material is placed in a vacuum drying oven and dried at 50°C to 80°C for 2 to 24 hours to remove residual solvents, and then heat treated at 100°C to 130°C (preferably 110°C to 120°C) for no more than 2 hours to further improve the mechanical and thermal stability of the material.

[0027] Application of a 3D printed functional protein nanocomposite material: The 3D printed iron oxide-functional protein nanocomposite material prepared by the present invention has excellent specific surface area and phosphorus adsorption sites, and is suitable for deep treatment of phosphorus-containing wastewater. The composite material can efficiently remove phosphorus ions in the presence of phosphorus as low as sub-trace concentrations, and can be regenerated multiple times after simple cleaning or low-temperature treatment, and is suitable for long-term water treatment applications. The method is simple to operate, low in cost, environmentally friendly and non-toxic, suitable for large-scale preparation, and provides an efficient and sustainable technical solution for the treatment of phosphorus pollution in water bodies. Example

[0028] A method for preparing a 3D printed functional protein nanocomposite material comprises the following steps: Step (1) Preparation of iron oxide-functional protein composite particles: The functional protein (such as lysozyme) is pretreated into a fibrous structure to increase the specific surface area to improve the loading capacity of iron oxide nanoparticles. Fe(NO3)3·9H2O is dissolved in deionized water to prepare a 0.8 M solution, mixed with the functional protein and transferred to an autoclave for reaction at 105°C for 3 hours. Iron oxide particles with a particle size of less than 10 nm are generated in situ during the reaction and are evenly distributed on the protein surface. After the reaction is completed, the mixture is cooled to room temperature, washed to remove impurities, and centrifuged (10,000 rpm) to obtain high-purity composite particles, which are then dried under vacuum at 80°C for 12 hours.

[0029] Step (2) 3D printing and heat treatment: The composite particles were dispersed in a 10% solution, PEG (3% by mass) was added as a dispersant, and ultrasonic dispersion was performed for 40 minutes. After printing, the particles were vacuum dried at 50°C for 8 hours, and then heat treated at 110°C for 2 hours to enhance the thermal stability and acid and alkali resistance of the material.

[0030] Performance: In the treatment of simulated phosphorus-containing wastewater (initial concentration 10 mg / L, pH 7.0 to 7.5), the composite material was stirred at a dosage of 0.5 g / L for 1 hour, and the phosphorus removal rate reached 92%. In the pH range of 2 to 12, the removal rate remained above 85%, and it still reached 90% after three cycles, showing excellent stability and durability. In comparison, the removal rate of traditional iron oxide particles was 75%, which dropped to 70% after three cycles; the removal rate of commercial activated carbon was 80%, which dropped to 75% after cycles; the removal rate of polyaluminium chloride was 78%, which dropped to 72% after cycles. The composite material is significantly superior to the control material in terms of removal efficiency, stability and cycle performance, reflecting its excellent practical application potential. Example

[0031] A method for preparing a 3D printed functional protein nanocomposite material comprises the following steps: Step (1) Preparation of iron oxide-functional protein composite particles: The functional protein (such as lysozyme) is pretreated into a fibrous structure to increase the specific surface area and improve the loading capacity of iron oxide nanoparticles. Fe(NO3)3·9H2O is dissolved in ethylene glycol to prepare a solution with a concentration of 0.9 M. After mixing with the functional protein, it is transferred to an autoclave and reacted at 110°C for 4 hours. Iron oxide particles with a particle size of less than 10 nm are generated in situ and evenly distributed on the protein surface. After the reaction, it is cooled to room temperature, washed to remove impurities, and centrifuged (10,000 rpm) to obtain high-purity composite particles, which are then dried under vacuum at 70°C for 12 hours.

[0032] Step (2) 3D printing and heat treatment: The composite particles were dispersed in a 10% solution, PEG was added as a dispersant (3% by mass), and ultrasonic dispersion was performed for 45 minutes. The dispersion was loaded into a light-curing 3D printing device, and appropriate exposure time, layer thickness, and scanning speed were set for printing. After printing, the material was vacuum dried at 60°C for 8 hours, and then heat treated at 120°C for 1 hour to enhance the mechanical strength and thermal stability of the material.

[0033] Performance: In the treatment of phosphorus-containing simulated wastewater (initial concentration 20 mg / L, pH 6.5 to 7.5), the composite material was stirred at a dosage of 0.6 g / L for 1 hour, and the phosphorus removal rate exceeded 95%. Under high temperature conditions of 60°C, the material removal performance did not decrease significantly, and the removal rate remained at 92% after three cycles, showing good high temperature stability and recycling performance. In contrast, the removal rate of traditional iron oxide particles was 78% under the same conditions, and the removal rate dropped to 72% under 60°C, and dropped to 68% after three cycles; the removal rate of commercially available activated carbon was 83%, which dropped to 78% under high temperature conditions and dropped to 74% after cycles; the removal rate of polyaluminium chloride was 80%, which dropped to 75% under high temperature conditions and dropped to 70% after cycles. The removal efficiency, stability and durability of the composite material under high temperature environment are significantly better than those of the control material, showing excellent practical application potential. Example

[0034] A method for preparing a 3D printed functional protein nanocomposite material comprises the following steps: Step (1) Preparation of iron oxide-functional protein composite particles: The functional protein (such as bovine serum albumin) is pretreated into a fibrous structure to increase the specific surface area and enhance the loading capacity of iron oxide nanoparticles. Fe(NO3)3·9H2O is dissolved in deionized water to prepare a 0.75 M solution, which is mixed with the functional protein and transferred to a high-pressure reactor for reaction at 105°C for 3 hours. Iron oxide particles with a particle size of less than 10 nm are generated in situ during the reaction and are evenly distributed on the protein surface. After the reaction is completed, the mixture is cooled to room temperature, washed to remove impurities, and centrifuged (10,000 rpm) to obtain high-purity composite particles, which are then vacuum dried at 50°C for 10 hours.

[0035] Step (2) 3D printing and heat treatment: The composite particles were dispersed in an 8% solution, PVP (4% by mass) was added as a dispersant, and ultrasonic dispersion was performed for 40 minutes. After printing by a light-curing 3D printing device, vacuum drying was performed at 40°C for 4 hours, and then heat treatment was performed at 100°C for 2 hours to improve the stability of the material.

[0036] Performance: In the treatment of phosphorus-containing simulated wastewater (initial concentration 15 mg / L, pH 7.0 to 7.5), the composite material was stirred at a dosage of 0.4 g / L for 90 minutes, and the phosphorus removal rate was still over 90% in a low temperature environment (5°C). After three cycles, the removal rate remained above 88%, showing excellent low-temperature adaptability and stability. In contrast, the removal rate of traditional iron oxide particles was 70% under the same conditions, which further dropped to 65% in a low-temperature environment and only 60% after three cycles; the removal rate of commercially available activated carbon was 75%, which dropped to 70% under low-temperature conditions and dropped to 68% after cycles; the removal rate of polyaluminium chloride was 72%, which dropped to 68% under low-temperature conditions and dropped to 65% after cycles. The removal efficiency, stability and durability of the composite material in a low-temperature environment are significantly better than those of the control material, demonstrating its application potential in special environments. Example

[0037] A method for preparing a 3D printed functional protein nanocomposite material comprises the following steps: Step (1) Preparation of iron oxide-functional protein composite particles: The functional protein (such as lysozyme) is pretreated into a fibrous structure to enhance its loading capacity for iron oxide nanoparticles. Fe(NO3)3·9H2O is dissolved in ethylene glycol to prepare a 1.0 M solution, which is mixed with the functional protein and transferred to an autoclave for reaction at 115°C for 5 hours. Iron oxide particles with a particle size of less than 10 nm are generated in situ during the reaction and are evenly distributed on the protein surface. After the reaction is completed, the mixture is cooled to room temperature, washed to remove impurities, and centrifuged (10,000 rpm) to obtain high-purity composite particles, which are then dried under vacuum at 80°C for 15 hours.

[0038] Step (2) 3D printing and heat treatment: The composite particles were dispersed in a 12% solution, polyvinyl alcohol (PVA) (5% by mass) was added as a dispersant, and ultrasonic dispersion was performed for 60 minutes. After printing, the composite particles were vacuum dried at 70°C for 12 hours and then heat treated at 130°C for 1.5 hours to enhance the stability and durability of the composite material.

[0039] Performance: In the treatment of phosphorus-containing simulated wastewater (initial concentration 50 mg / L, pH 6.5 to 7.0), the composite material was stirred at a dosage of 1.0 g / L for 30 minutes, and the phosphorus removal rate was as high as 98%. In a high salinity environment (NaCl concentration 100 g / L) and high temperature conditions (45°C), the removal rate remained above 94%, showing excellent salt resistance and thermal stability, providing important support for the treatment of complex water bodies. In contrast, the removal rate of traditional iron oxide particles dropped to 78% in high salinity and further dropped to 75% under high temperature conditions; the removal rate of commercially available activated carbon was 82%, which dropped to 80% and 78% under high salinity and high temperature environments respectively; the removal rate of polyaluminium chloride was 80%, which dropped to 76% and 74% under high salinity and high temperature conditions respectively. The removal efficiency and stability of the composite material in complex environments are significantly better than those of traditional materials, highlighting its practical value in the treatment of high-salinity and high-temperature water bodies. Example

[0040] A method for preparing a 3D printed functional protein nanocomposite material comprises the following steps: Step (1) Preparation of iron oxide-functional protein composite particles: The functional protein (such as lysozyme) is pretreated into a fibrous structure to enhance its loading capacity for iron oxide nanoparticles. Fe(NO3)3·9H2O is dissolved in deionized water to prepare a 0.75M solution, mixed with the functional protein and transferred to a high-pressure reactor for reaction at 105°C for 3 hours. Iron oxide particles with a particle size of less than 10 nm are generated in situ during the reaction and are evenly distributed on the protein surface. After the reaction is completed, it is cooled to room temperature, washed to remove impurities, and centrifuged (10,000 rpm) to obtain high-purity composite particles, which are then vacuum dried at 60°C for 10 hours.

[0041] Step (2) 3D printing and heat treatment: The composite particles were dispersed in a 10% solution, PEG (3% by mass) was added as a dispersant, and ultrasonic dispersion was performed for 30 minutes. After printing by a light-curing 3D printing device, the particles were vacuum dried at 60°C for 8 hours, and then heat treated at 110°C for 1 hour to enhance the performance of the material.

[0042] Performance: In the treatment of low-phosphorus concentration simulated wastewater (initial concentration 5 mg / L, pH 7.0 to 7.5), the composite material was stirred at a dosage of 0.3 g / L for 1 hour, and the phosphorus removal rate reached 92%. Under different water quality conditions, the composite material showed good deep phosphorus removal ability and was suitable for efficient treatment of low-concentration phosphorus wastewater. In contrast, the removal rate of traditional iron oxide particles under the same conditions was only 70%; the removal rate of commercially available activated carbon was 75%; and the removal rate of polyaluminum chloride was 72%. These control materials showed low efficiency limitations in low-phosphorus concentration environments, while the composite material was significantly superior in removal efficiency, showing excellent deep treatment capabilities and practical application potential. Example

[0043] A method for preparing a 3D printed functional protein nanocomposite material comprises the following steps: Step (1) Preparation of iron oxide-functional protein composite particles: The functional protein (such as bovine serum albumin) is pretreated into a fibrous structure to enhance its loading capacity for iron oxide nanoparticles. Fe(NO3)3·9H2O is dissolved in ethylene glycol to prepare a 0.75 M solution, mixed with the functional protein and transferred to a high-pressure reactor for reaction at 110°C for 4 hours. Iron oxide particles with a particle size of less than 10 nm are generated in situ during the reaction and are evenly distributed on the protein surface. After the reaction is completed, the mixture is cooled to room temperature, washed to remove impurities, and centrifuged (10,000 rpm) to obtain high-purity composite particles, which are then dried under vacuum at 70°C for 10 hours.

[0044] Step (2) 3D printing and heat treatment: The composite particles were dispersed in a 10% solution, PEG (3% by mass) and PVP (5% by mass) were added as dispersants, and ultrasonic dispersion was performed for 50 minutes. After printing, the particles were vacuum dried at 60°C for 12 hours, and then heat treated at 120°C for 1.5 hours to enhance the stability and removal performance of the composite material.

[0045] Performance: When PVP was used as a dispersant, the composite material was stirred in phosphorus-containing wastewater (initial concentration 10 mg / L, pH 7.0 to 7.5) at a dosage of 0.5 g / L for 1 hour, and the phosphorus removal rate reached more than 96%. In contrast, the removal rate of the composite material using PEG as a dispersant was 85%, while the removal rate of the composite material without the addition of a dispersant was only 78%. This result shows that the choice of dispersant has a significant effect on the phosphorus removal performance of the composite material, and PVP is particularly outstanding in improving the removal efficiency, providing important guidance for optimizing the performance of the composite material.

[0046] The key steps of the preparation method of the present invention include: first, a functional protein (such as bovine serum albumin or lysozyme protein) is converted into an ultra-long flexible amyloid fiber structure by a self-assembly method, which has a highly abundant amino group and good metal loading capacity. Subsequently, the high coordination ability of the functional protein material with iron is used to generate sub-10 nm iron oxide nanoparticles in situ on the surface of the fiber structure to ensure the uniform distribution and effective loading of the nanoparticles. The nanoparticles not only have controllable particle size and good dispersibility, but also significantly improve the stability and reusability of the material through the physical support of the functional protein. In the molding process of the material, the present invention adopts 3D printing technology to achieve controllable design of the macroscopic structure of the composite material. By precisely controlling 3D printing parameters such as printing temperature, nozzle diameter and interlayer stacking angle, the optimized layout of the pore structure, specific surface area and adsorption sites of the material can be achieved, thereby effectively improving its adsorption performance and regeneration ability. Further post-treatment steps can enhance the structural strength and chemical stability of the material by thermal curing or surface modification, so that it still has excellent performance in complex water environments. Compared with the traditional preparation method, the preparation process of the present invention does not require complex dispersants or toxic and harmful solvents, meets environmental protection requirements, and has green and low-carbon advantages. In addition, due to the high flexibility of 3D printing technology, this method can quickly adjust the material structure and size according to application requirements, is suitable for large-scale production, and has significant economic efficiency. The composite material shows broad application prospects in the deep removal of phosphorus, industrial wastewater treatment and resource recovery, and provides an innovative solution for water purification.

[0047] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes can be made to them in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art can make their own changes and modifications without departing from the spirit and scope of the present application, so the scope of protection of the present application shall be based on the scope defined in the claims.

Claims

1. A method for preparing a 3D printed functional protein nanocomposite material, characterized in that: The following steps are involved: Step (1) in situ generation of iron oxide-functional protein composite particles: pre-treating the functional protein into a fibrous amyloid structure; The iron salt solution is mixed with the material pretreated with the functional protein, and reacted under a high temperature and high pressure environment of 105° C. to 115° C. for 3 to 5 hours, so that the iron oxide nanoparticles with a particle size of less than 10 nanometers are evenly distributed on the surface of the functional protein fiber matrix, thereby obtaining the functional protein-loaded iron oxide nanoparticles; Step (2) 3D printing and heat treatment: dispersing the functional protein-loaded iron oxide nanoparticles in a stable dispersion, and forming a composite material with a controllable pore structure through a 3D printing device; vacuum drying and heat treating the printed composite material to enhance the mechanical properties and chemical stability of the composite material.

2. The preparation method according to claim 1, characterized in that: The iron salt used in step (1) is Fe(NO3)3·9H2O, which is dissolved in ethylene glycol or deionized water, and the solution concentration is 0.5 to 1.25 M, preferably in the range of 0.75 to 1.0 M.

3. The preparation method according to claim 1, characterized in that: The concentration of the dispersion in step (2) is 5% to 15%, and a dispersing aid accounting for 1% to 10% of the mass of the iron oxide is added to enhance the uniform distribution of the particles.

4. The preparation method according to claim 3, characterized in that: The dispersing aid is polyethylene glycol or polyvinyl pyrrolidone, and the dispersing aid accounts for 3% to 5% of the mass of the iron oxide.

5. The preparation method according to claim 1, characterized in that: The 3D printing parameters in step (2) include an exposure time of 1 to 10 seconds and a layer thickness of 0.01 to 0.1 mm.

6. The preparation method according to claim 1, characterized in that: The heat treatment temperature in step (2) is 100° C. to 130° C., and the treatment time is less than 2 hours.

7. An application of the 3D printed functional protein nanocomposite material according to any one of claims 1 to 6, characterized in that: Treatment of phosphorus-containing wastewater.

Citation Information

Patent Citations

  • Fibroin-controlled alpha type ferric oxide nano material and preparation method thereof

    CN102649589A

  • Nanocrystalline iron oxide-based magnetic material for 3D printing and preparing method thereof

    CN104200948A

  • Method for preparing alpha-Fe2O3 mesoscopic crystal having controllable morphology by using protein as template

    CN105236495A

  • Magnetic nano-particles coated with water-soluble protein and preparation method of magnetic nano-particles

    CN105288666A

  • Loading structure for adsorbing heavy metal pollutants and preparation method and application thereof

    CN109603746A